Analysis of the effect of search step size on the accuracy and convergence properties of electromagnetism-like mechanism algorithm - Tan J.D.; Dahari M.; Koh S.P.; Koay Y.Y.; Abed I.A. (Old City Publishing, 2023)
Benchmarking; Global optimization; Convergence performance; Convergence properties; Electromagnetism-like mechanism algorithms; Global optimization problems; Meta-heuristic search algorithms; Metaheuristic; Modified algorithms; Search steps; Optimization